FORMATION OF INTELLECTUAL TECHNIQUE OF A SPECIALIST ON THE BASIS OF MATHEMATICAL CATEGORIES - Смага, Лариса (Socio-economic relations in the digital society, 2020)
The main types and levels of mathematical competence used to study mathematical disciplines in economic universities are researched. The issues of scientific, technical and socio-economic development of modern society, improvement and full implementation in everyday practice of the latest communication technologies, the use of which can significantly increase the efficiency of computer processes: systematization, collection, processing, analysis, storage, generalization, search, transmission and presentation of various data and information. The ways and conditions of effective introduction of new communication technologies in the educational process to improve the quality of knowledge and the level of training of future economists are proposed. Having analyzed the theoretical and practical part of the mathematical training of future specialists in the financial and credit sphere, the main functions of the application of computer technology in education are identified: the organization of cognitive activity by the method of internal and external modeling; creation of new methods of educational process; timely correction and control of the system of educational activities; modeling of joint activity of teacher and student. The use of computer technology systems in the study of mathematical disciplines will significantly increase the mathematical education of students in economic universities. The use of information and computer technology in the study of mathematical disciplines contributes to changes in norms, methods and content of education. In accordance with the tasks of training specialists taking into account the requirements of the state standard of education and in order to improve the efficiency of education, the structure of the content of studying the block of mathematical disciplines for students of economics with the use of modern computer technology.